PENYELESAIAN PELANGGARAN LARANGAN KAWIN SATU SUKU BERDASARKAN HUKUM ADAT MELAYU PETALANGAN PADA MASYARAKAT ADAT DESA TAMBAK KABUPATEN PELALAWAN - Emilia Hidayani; Rika Lestari; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Same-ethnic marriage is a ban on marriage in the indigenous people of Tambak Village,Langgam District. This is because the customary law system views same-ethnic marriages asmarriages that occur within one family or one breastfeeding. The indigenous people of Tambak,Langgam District, are still guided by the fatwas from their ancestors. So in this case the indigenouspeople in Tambak Village, Langgam District, still prohibit same-tribe marriage. The purpose of thisthesis research is first, the factors that cause same-tribal marriage in indigenous peoples in TambakVillage, Langgam District, Pelalawan Regency. Second, settlement of violations of the prohibitionon same-tribal marriages committed by traditional leaders in the indigenous people of TambakVillage, Langgam District, Pelalawan Regency.This type of research can be classified into the type of sociological juridical research. Withthe research location in Tambak Village, Langgam District, Pelalawan Regency. While thepopulation and sample are parties related to the problem under study. This study used primary datasources and secondary data and data collection techniques were carried out by means of interviewsand literature review.The results of the research conducted by the author are, First, the causes of one-tribemarriage in indigenous peoples in Tambak Village, Langgam District, Pelalawan Regency arecaused by a lack of understanding of customs and tribes in Tambak Village, Langgam District,Pelalawan Regency; decreased public compliance; Affection and mutual love; law is defeated bytime; Because in Islamic law there are no rules governing the prohibition of same-ethnic marriages.Second, the settlement of violations of the prohibition on same-tribal marriages perpetrated bytraditional leaders in the indigenous people of Tambak Village, Langgam District, PelalawanRegency can be carried out by means of the customary leader (datuk shoot inner/penghulu) carryingout clarification of couples who violate customary same-tribal marriages; listen to explanations orclarifications by perpetrators of ethnic marriage offenders; customary leaders will deliberate toreach a consensus/decision; after finding a consensus, the traditional leader conveys the customarysayings and inner shoots conveys their attitudes and decisions; sanctions for violators of sameethnic marriages, namely expulsion from the village; if the violator asks for forgiveness, he must pay1 (one) buffalo along with other equipment; paying customary fines by feeding 1 (one) Nagari; ifthe customary fine has been paid, the offender of the same ethnic marriage has been reinstated. Theauthor's suggestion is that traditional leadersandthe role of parent return to actively holdingcustomary meetings involving all elements of the village community, including the youngergeneration, so that traditional values that have been passed down from generation to generation canbe re-instilledKeywords: Prohibition, Same-Ethnic Marriage, Indigenous Peoples